Elongator: transcriptional or translational regulator? - Glatt, Sebastian; Séraphin, Bertrand; Müller, Christoph W. (Transcription)
The conserved multi-subunit Elongator complex was initially described as a RNA polymerase II (RNAPII) associated transcription elongation factor, but since has been shown to be involved a variety of different cellular activities. Here, we summarize recent developments in the field and discuss the resulting implications for the proposed multi-functionality of Elongator.